The combination of carboxy‐terminal propeptide of procollagen type I blood levels and late gadolinium enhancement at cardiac magnetic resonance provides additional prognostic information in idiopathic dilated cardiomyopathy – A multilevel assessment of myocardial fibrosis in dilated cardiomyopathy - Raafs, Anne G.; Verdonschot, Job A.J.; Henkens, Michiel T.H.M.; Adriaans, Bouke P.; Wang, Ping; Derks, Kasper; Abdul Hamid, Myrurgia A.; Knackstedt, Christian; Empel, Vanessa P.M.; Díez, Javier; Brunner‐La Rocca, Hans‐Peter; Brunner, Han G.; et al. (European journal of heart failure, 2021)
Aims To determine the prognostic value of multilevel assessment of fibrosis in dilated cardiomyopathy (DCM) patients. Methods and results We quantified fibrosis in 209 DCM patients at three levels: (i) non‐invasive late gadolinium enhancement (LGE) at cardiac magnetic resonance (CMR); (ii) blood biomarkers [amino‐terminal propeptide of procollagen type III (PIIINP) and carboxy‐terminal propeptide of procollagen type I (PICP)], (iii) invasive endomyocardial biopsy (EMB) (collagen volume fraction, CVF). Both LGE and elevated blood PICP levels, but neither PIIINP nor CVF predicted a worse outcome defined as death, heart transplantation, heart failure hospitalization, or life‐threatening arrhythmias, after adjusting for known clinical predictors [adjusted hazard ratios: LGE 3.54, 95% confidence interval (CI) 1.90–6.60; P < 0.001 and PICP 1.02, 95% CI 1.01–1.03; P = 0.001]. The combination of LGE and PICP provided the highest prognostic benefit in prediction (likelihood ratio test P = 0.007) and reclassification (net reclassification index: 0.28, P = 0.02; and integrated discrimination improvement index: 0.139, P = 0.01) when added to the clinical prediction model. Moreover, patients with a combination of LGE and elevated PICP (LGE+/PICP+) had the worst prognosis (log‐rank P < 0.001). RNA‐sequencing and gene enrichment analysis of EMB showed an increased expression of pro‐fibrotic and pro‐inflammatory pathways in patients with high levels of fibrosis (LGE+/PICP+) compared to patients with low levels of fibrosis (LGE‐/PICP‐). This would suggest the validity of myocardial fibrosis detection by LGE and PICP, as the subsequent generated fibrotic risk profiles are associated with distinct cardiac transcriptomic profiles. Conclusion The combination of myocardial fibrosis at CMR and circulating PICP levels provides additive prognostic value accompanied by a pro‐fibrotic and pro‐inflammatory transcriptomic profile in DCM patients with LGE and elevated PICP. Multilevel assessment of myocardial fibrosis demonstrates significant correlations between histology, non‐invasive imaging, and blood markers. A combined multi‐parametric approach with carboxy‐terminal propeptide of procollagen type I (PICP) and late gadolinium enhancement (LGE) allows the best risk stratification of idiopathic dilated cardiomyopathy (DCM) patients, accompanied with a profile of high expression of combined pro‐inflammatory and pro‐fibrotic genes, indicating a potential marker for disease activity.